A pilot study comparing the DuoFertility® monitor with ultrasound in infertile women - Rollason JCB; Outtrim JG; Mathur RS (Dove Medical Press, 2014)
Jennie CB Rollason,1 Joanne G Outtrim,2 Raj S Mathur1 1Cambridge IVF, Addenbrooke's NHS Trust, 2University Division of Anaesthesia, University of Cambridge, Addenbrooke's Hospital, Cambridge, UK Background: The purpose of this study was to assess the accuracy of ovulation detection by the DuoFertility® monitor compared with transvaginal ultrasound in infertile women with regular menstrual cycles. Methods: Eight infertile patients, aged 27–40 years, with a body mass index of 19–29, regular menses, normal ovaries on pelvic ultrasound scan, and normal early follicular luteinizing hormone (LH), follicle-stimulating hormone, and prolactin were recruited from infertility clinics in primary and secondary care for this pilot, prospective, observational study. The patients were asked to use the DuoFertility monitor for the whole cycle, with investigators and patients blind to DuoFertility data. Daily urine LH monitoring commenced on cycle day 8, with daily transvaginal ultrasound following the first positive LH until ovulation was observed. Ovulation was further confirmed by serum progesterone. The main outcome measure was detection of ovulation by the DuoFertility monitor, and correlation between day of ovulation assessed by DuoFertility and ultrasound. Results: DuoFertility identified ovulation as having occurred within one day of that determined via ultrasound in all cycles. The sensitivity of ovulation detection was 100% (95% confidence interval 82–100). The specificity could not be concluded from the data. Conclusion: In infertile women with regular cycles, the DuoFertility monitor appears to accurately identify ovulatory cycles and the day of ovulation. Keywords: fertility monitor, ovulation, infertility, ultrasound scan, urinary luteinizing hormone